2012
DOI: 10.1105/tpc.112.100495
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium May Delay Plant Nonhomologous End-Joining DNA Repair via XRCC4 to Favor T-DNA Integration

Abstract: Agrobacterium tumefaciens is a soilborne pathogen that causes crown gall disease in many dicotyledonous plants by transfer of a portion of its tumor-inducing plasmid (T-DNA) into the plant genome. Several plant factors that play a role in Agrobacterium attachment to plant cells and transport of T-DNA to the nucleus have been identified, but the T-DNA integration step during transformation is poorly understood and has been proposed to occur via nonhomologous end-joining (NHEJ)-mediated doublestrand DNA break (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 55 publications
1
33
0
Order By: Relevance
“…Vaghchhipawala et al . () explained transformation hyper‐susceptibility of a XRCC4 down‐regulated Arabidopsis line as a consequence of slower joining of either naturally occurring dsDNA breaks, or breaks induced by the stress of incubating plant cells with agrobacteria; the data presented in this paper are consistent with this interpretation. Slower break processing and sealing would provide increased opportunity for T‐DNA ligation to the broken ends of plant DNA and mirrors the enhancement of transformation upon induction of DNA damage in protoplasts (Köhler et al ., ).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Vaghchhipawala et al . () explained transformation hyper‐susceptibility of a XRCC4 down‐regulated Arabidopsis line as a consequence of slower joining of either naturally occurring dsDNA breaks, or breaks induced by the stress of incubating plant cells with agrobacteria; the data presented in this paper are consistent with this interpretation. Slower break processing and sealing would provide increased opportunity for T‐DNA ligation to the broken ends of plant DNA and mirrors the enhancement of transformation upon induction of DNA damage in protoplasts (Köhler et al ., ).…”
Section: Discussionsupporting
confidence: 74%
“…However, roots are the natural target for Agrobacterium ‐mediated transformation. Two studies in which roots were infected showed no reduction in transformation frequency using lig4 , ku70 , or ku80 mutants (van Attikum et al ., ; Jia et al ., ) and another study indicated that reduced XRCC4 expression in Arabidopsis and Nicotiana benthamiana increased stable transformation and T‐DNA integration (Vaghchhipawala et al ., ). Recently, Mestiri et al .…”
Section: Discussionmentioning
confidence: 97%
“…tumefaciens (Friesner and Britt, 2003;Gallego et al, 2003). However, in other studies, contradictory data indicated that Arabidopsis ku80 or ku70 (At1g16970) mutant plants and rice plant lines downregulated in ku70, ku80, or lig4 showed different transformation responses (van Attikum et al, 2001;Friesner and Britt, 2003;Gallego et al, 2003;Li et al, 2005b;Jia et al, 2012;Nishizawa-Yokoi et al, 2012;Vaghchhipawala et al, 2012;Mestiri et al, 2014;Park et al, 2015). These discrepancies might be the result of different techniques and different plant tissues used to examine transformation efficiency, or they may reveal more complex and redundant pathways for T-DNA integration mechanisms during A. tumefaciens infections (Tzfira et al, 2004a;Citovsky et al, 2007;Gelvin, 2010aGelvin, , 2010bMagori and Citovsky, 2012;Lacroix and Citovsky, 2013).…”
Section: Integration Into the Plant Genome And Expression Of The T-dnamentioning
confidence: 99%
“…Integration and/ or expression of T-DNA AtLIG4 (DNA ligase IV) At5g57160 Ziemienowicz et al, 2000;Friesner and Britt, 2003;van Attikum et al, 2003;Zhu et al, 2003a;Nishizawa-Yokoi et al, 2012;Park et al, 2015KU80 At1g48050 van Attikum et al, 2001Friesner and Britt, 2003;Gallego et al, 2003;Li et al, 2005b;Nishizawa-Yokoi et al, 2012;Jia et al, 2012;Mestiri et al, 2014;Park et al, 2015KU70 At1g16970 van Attikum et al, 2001Li et al, 2005b;Nishizawa-Yokoi et al, 2012;Jia et al, 2012;Mestiri et al, 2014;Park et al, 2015 MRE11 (meiotic recombination 11) At5g54260 van Attikum et al, 2001;Jia et al, 2012; XRCC1 (homolog of X-ray repair cross complementing 1) At1g80420 Mestiri et al, 2014;Park et al, 2015 XRCC2 (homolog of X-ray repair cross complementing 2) At5g64520 Mestiri et al, 2014;Park et al, 2015 XRCC4 (homolog of X-ray repair cross complementing 4) At3g23100 Vaghchhipawala et al, 2012;Park et al, 2015 XPF/RAD1/UVH1 (ultraviolet hypersensitive 1) At5g41150 Nam et al, 1998;Mestiri et al, 2014;Park et al, 2015 PARP1 (poly(ADP-ribose) polymerases 1) At2g31320 Jia et al, 2012;Park et al, 2015 HTA1 (histone H2A) At5g54640 Nam et al, 1999;Mysore et al, 2000a, b;Yi et al, 2002Yi et al, , 2006…”
Section: Referencesmentioning
confidence: 99%
“…The mutants lacking NHEJ-related genes ku70, ku80, and especially the lig4 mutant presented a reduction in frequency of stable transformation [137]. In tobacco, the role of XRCC4, another NHEJ factor, was observed in a complex with Lig4 to seal the two ends of the DSB during in the T-DNA integration [138]. In this work, it was also observed by yeast twohybrid assay that the protein VirE2 (from Agrobacterium) interacts with XRCC4, then it is proposed that the VirE2 protein may act in the inactivation of XRCC4, then delaying the final step of NHEJ repair, creating an opportunity for T-DNA integration [138].…”
Section: Non-homologous End Joining (Nhej)mentioning
confidence: 99%